Laparoscopic and open right‐sided colonic resection in daily routine practice. A prospective multicentre study within an Enhanced Recovery After Surgery (ERAS) protocol. (2nd February 2016) - Tiefenthal, M.; Asklid, D.; Hjern, F.; Matthiessen, P.; Gustafsson, U. O.
Abstract: Aim: The study compared the outcome of laparoscopic and open surgery in daily practice when performed in a strict Enhanced Recovery After Surgery (ERAS) environment. Method: Two‐hundred and ninety‐two consecutive patients who received elective surgery, in three Swedish ERAS centres, for cancer or adenoma in the right colon in the period 1 January 2011 to 31 December 2012, were prospectively registered in a Web‐based ERAS database. Peri‐operative data were collected from the database and patient charts. The primary end‐points included postoperative recovery and morbidity. The secondary objective was to identify preoperative variables that influenced the selection of patients for laparoscopic or open surgery. Results: One‐hundred and twenty‐three (42%) patients were selected for laparoscopic surgery. The overall preoperative ERAS‐compliance rate was 87% and no significant difference was seen between the surgical techniques. In multivariate analysis, patients treated with laparoscopy had significantly earlier pain control (2.4 ± 3.2 days vs 4.2 ± 5.9 days; P  = 0.016) and a shorter length of hospital stay (LOS) (4 days vs 6 days; P  = 0.002) compared with open surgery. There was no significant difference in the complication rate [18.7% vs 21.3%; OR = 1.0 (95% CI: 0.5–2.0)], the number of lymph nodes removed or the rate of R0 resection between laparoscopic and open surgery. Tumours selected for laparoscopy were generally smaller, had a lower T‐stage and were predominantly situated in the caecum and the ascending colon compared with those of patients selected for open surgery. Conclusion: The use of laparoscopy in routine right‐sided colectomy in an ERAS environment, with data on outcome corrected for selection bias, may result in faster recovery compared with open surgery.